Combining Reflectance Confocal Microscopy, Optical Coherence Tomography, and Ex-Vivo Fluorescence Confocal Microscopy for Margin Assessment in Basal Cell Carcinoma Excision - Michelini, Simone; Mandel, Victor Desmond; Ardigò, Marco; Ciardo , Silvana; Cota, Carlo; Cesinaro, Anna Maria; Rossi, Elena; Ferrari, Barbara; Kaleci, Shaniko; Di Fraia, Marco; Chello, Camilla; Cantisani, Carmen; et al. (Dermatology Practical & Conceptual, 2026)
Introduction: Recent developments of noninvasive, high-resolution imaging techniques, such as reflectance confocal microscopy (RCM) and optical coherence tomography (OCT), have enhanced skin cancer detection and precise tumor excision particularly in highly aggressive and poorly defined basal cell carcinomas (BCCs)Objectives: The aim of this pilot study is to assess feasibility and reproducibility of a systematic clinical workflow combining noninvasive (RCM-OCT) and invasive fluorescence confocal microscopy (FCM) imaging modalities in pre- and intra-surgical evaluations of lateral and deep margins of BCC.Methods: Superficial incisions were made 2 mm beyond the clinical-dermoscopic BCC margins. Lateral margins were then explored with OCT and RCM. In positive margins, a further cut was made 2 mm distal from the previous. A final RCM/OCT-based double-negative margin was drawn around the entire perimeter of the lesion before referring to surgery. The freshly excised specimen was then examined with FCM (ex-vivo) for the evaluation of the deep margin. Histopathologic examination eventually confirmed margin involvement.Results: The study included 22 lesions from 13 patients. At the end of the study, 146 margins—106 negative (73%) and 40 positive (27%) at RCM/OCT—were collected. RCM/OCT margin evaluation showed an overall sensitivity of 100%, a specificity of 96.3%. The overall positive margins diagnostic accuracy was 98.2%. Reproducibility was evaluated on recorded images and the raters showed a substantial inter-observer agreement on both RCM (κ =0.752) and OCT images (κ =0.724).Conclusions: The combined RCM/OCT/FCM ex-vivo approach noninvasively facilitates the presurgical and intrasurgical lateral and deep margin assessment of poorly defined BCCs.